CXCR1/2 Chemokine Network Regulates Melanoma Resistance to Chemotherapies Mediated by NF-ΚB - Wu, S.; Saxena, S.; Varney, M.L.; Singh, R.K. (Current Molecular Medicine, 2017)
Background: Cancer-related inflammation is recognized as a driver for tumor progression and chemokines are important players in both inflammation and the progression of many cancer types. CXC chemokines, especially CXCL8, have been implicated in melanoma growth and metastasis, while less is known for their roles in drug resistance. Methods: We generated drug-resistant cells by continuous exposure to chemotherapeutic drugs and analyzed the mechanism(s) of therapy resistance in malignant melanoma. Results: We report chemotherapies induced upregulation of a variety of chemokines in the CXCR1/CXCR2 network by an NF-ΚB-dependent mechanism. Notably, analysis of the drug-resistant melanoma cell line selected after prolonged exposure to chemotherapeutic drug dacarbazine revealed higher levels of CXCL8 and CXCR2 compared with parent cells as a signature of drug resistance. CXCR2 neutralization markedly improved sensitivity to dacarbazine in melanoma cells. Conclusion: These data provide insights into what drives melanoma cells to survive after chemotherapy treatment, thus pointing to strategies for developing combined drug therapies for combating the problem of chemotherapy resistance in melanoma.
Keywords: resistance